Representasi Fear of Missing Out (FOMO) dalam Strategi Promosi Umrah - Ryan Firdiansyah Suryawan; Suharto Abdul Madjid; Yosi Pahala; Kamsariaty Kamsariaty; Nanda Pramana Putra (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the influence of Fear of Missing Out (FoMO)-based marketing strategies on Umrah consumer decision-making in the digital era. FoMO as a psychological phenomenon that develops due to the use of social media has been shown to influence consumption behavior widely, including in the context of religious travel. Methodology/approach: The approach used in this study is qualitative with a literature study method, examining relevant research results from internationally reputable journals for the last five years. Previous research has shown that FoMO correlates positively with purchase intent, especially through temporary marketing content and the role of social media influencers. Results/findings: In the context of Umrah, a promotional strategy that emphasizes quota limitations, departure times, and testimonials from previous pilgrims is able to create a perception of urgency and emotional attachment of potential consumers. This study concludes that FoMO can be an important variable in crafting marketing strategies that are more effective and relevant to today's digital Muslim generation. Conclusion: FoMO significantly shapes consumer behavior in umrah travel, where urgency-based marketing and digital content enhance purchase intention. However, its application should be sensitively aligned with spiritual values and community togetherness, not merely emotional pressure. Limitations: Limited to only variables FOMO, Marketing Strategy, Promotion, Consumer, Umrah, Qualitative Studies with the results. Contribution: The contribution of this research lies in the integration of digital psychology perspectives, religious consumer behaviuor, and ethical marketing strategies, as well as providing direction for further research and practical implications for the Umrah travel service industry players.